The Linguistic Attenuation in the Dramatic Text:The Script of Confessing to Laura - Vallejo Zapata, Víctor Julián; Zuluaga Gómez, Francisco Octavio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research article describes the pragmalinguistic phenomena in the script of the film Confession to Laura (Cardona, 2010), understanding it as a dramatic text type, close although different from the theatrical text. For coding the data, the attenuation sheet developed by the group Val.Es.Co (2013) is used with some modifications derived from the textual typology analyzed. Descriptive statistics are used to analyze the data and relevant elements are pointed out for understanding the corpus. It is concluded that the method designed by Val.Es.Co is relevant to fictional discourses and recommendations for future work are given